Gut microbiomes of free‐ranging and captive Namibian cheetahs: Diversity, putative functions and occurrence of potential pathogens. Issue 20 (8th September 2017) - Wasimuddin,; Menke, Sebastian; Melzheimer, Jörg; Thalwitzer, Susanne; Heinrich, Sonja; Wachter, Bettina; Sommer, Simone
Abstract: Although the significance of the gut microbiome for host health is well acknowledged, the impact of host traits and environmental factors on the interindividual variation of gut microbiomes of wildlife species is not well understood. Such information is essential; however, as changes in the composition of these microbial communities beyond the natural range might cause dysbiosis leading to increased susceptibility to infections. We examined the potential influence of sex, age, genetic relatedness, spatial tactics and the environment on the natural range of the gut microbiome diversity in free‐ranging Namibian cheetahs ( Acinonyx jubatus ). We further explored the impact of an altered diet and frequent contact with roaming dogs and cats on the occurrence of potential bacterial pathogens by comparing free‐ranging and captive individuals living under the same climatic conditions. Abundance patterns of particular bacterial genera differed between the sexes, and bacterial diversity and richness were higher in older (>3.5 years) than in younger individuals. In contrast, male spatial tactics, which probably influence host exposure to environmental bacteria, had no discernible effect on the gut microbiome. The profound resemblance of the gut microbiome of kin in contrast to nonkin suggests a predominant role of genetics in shaping bacterial community characteristics and functional similarities. We also detected various Operational Taxonomic Units (OTUs) assigned to potential pathogenic bacteria known to cause diseases in humans and wildlife species, such as Helicobacter spp., and Clostridium perfringens . Captive individuals did not differ in their microbial alpha diversity but exhibited higher abundances of OTUs related to potential pathogenic bacteria and shifts in disease‐associated functional pathways. Our study emphasizes the need to integrate ecological, genetic and pathogenic aspects to improve our comprehension of the main drivers of natural variation and shifts in gut microbial communities possibly affecting host health. This knowledge is essential for in situ and ex situ conservation management.